LITERACY SKILLS: CHARACTER, CITIZENSHIP, CRITICAL THINKING, CREATEMPATITY, COLLABORATION, COMMUNICATION (6C) OF ELEMENTARY SCHOOL STUDENTS - Minsih (PUPIL: International Journal of Teaching, Education and Learning, 2026)
The purpose of this study was to describe the 6C literacy skills of elementary school students at MI Muhammadiyah Kartasura, Sukoharjo. The research method was qualitative with a phenomenological design involving MI Muhammadiyah Special Program Schools. The subjects of this study were one principal and seven teachers at MI Muhammadiyah Kartasura, who participated in the pilot study. Data collection was conducted through focus group discussions (FGDs), interviews, observations, and documentation studies. Data validity was validated using source and technical triangulation. Sources came from informants and practitioners/academic experts. Data analysis used the Cresswell model, which includes data centralization, data description, and conclusion drawing. The results of the study indicate that the 6C literacy skills of elementary school students at MI Muhammadiyah Kartasura have entered a good level because the learning activities are carried out with the following steps: The literacy skills of MI Muhammadiyah PK students are obtained through several aspects, namely: Character: Demonstrating responsibility for literacy tasks, Citizenship: Linking material to local/community values, Critical Thinking: Being able to ask "why" and "how", Comparing two pieces of information and Providing reasons for opinions. Creativity: Producing original work, Collaboration: Playing an active role in groups, Communication: Conveying ideas verbally in a coherent manner. These activities are integrated into the teaching and learning process in class by using technology-based learning media that require students to interact with each other in class.